Nursing Leadership and Its Influence on Patient Care Quality and Public Health Outcomes - Mshari Aziz Hasen Alhakmi,; Kaif M J Al-Sokary,; Abdullah Yahya Abdullah Alasmari,; Sameer Awad Jaber Alsalmi,; Hammad Fawzan Hammad Alotaibi,; Ahmed Mohammed A AlShahri,; Mosa Hamed Mohammed Almalki,; Khalid Mohammed Dakhel Alshahrani,; Ali Yahya Mohammed Alwadei,; Ahmad Yahya Ahmad ALZahrani,; Mansour Mohammed Aldunayyish,; Hamid Ahmed Althagafy, (International Journal of Medical Toxicology and Legal Medicine, 2024)
Introduction: The public health status for the care of patients depends a lot on the nursing leadership that is present in the organization. Nursing leaders impact various parameters that characterize the nature of health care delivery systems today such as patient satisfaction, patient safety and the health care organization’s performance. Therefore the call for leadership in nursing has been propelled in recent years as healthcare organizations operating under new and ever-changing demands of patient needs and the constantly evolving healthcare systems across the globe. Aim of work: To investigate the influence of nursing leadership on patient care quality and public health outcomes. Methods: We conducted a comprehensive search in the MEDLINE database's electronic literature using the following search terms: Nursing, Leadership, Influence, Patient Care, Quality, Public Health, Outcomes. The search was restricted to publications from 2016to 2024 in order to locate relevant content. We performed a search on Google Scholar to locate and examine academic papers that pertain to my subject matter. The selection of articles was impacted by certain criteria for inclusion. Results: The publications analyzed in this study encompassed from 2016 to 2024. The study was structured into various sections with specific headings in the discussion section. Conclusion:In conclusion, nursing leadership is the central aspect of patient care and population health. Structurally, nurse leaders provide positive influences on the health care system affecting patient political climate on three levels by setting patient centered care standards, supporting nursing staff, and demanding health care policies that reduce health disparities. The continual fostering of capacities about nursing leadership is crucial to enhance the systems of healthcare with patients’ emphasis as well as to create health systems that would be ready for future challenges.